Synthesis Of Silver Nanoparticles Using Beluntas Leaf (Pluchea Indica L.) Extract - Fatimah Fatimah; Abdul Wahid Wahab; Abdul Karim (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Synthesis of silver nanoparticles was carried out using environmentally Beluntas (Pluchea Indica L.) leaf extract to minimize the use of harmful chemicals. Synthesis was carried out with the ratio of AgNO3 solution and the beluntas leaf extract 90 mL : 1 mL. The process of forming silver nanoparticles was studied and monitored by observing the absorption spectrum using UV-Vis spectrophotometer. The observations showed the silver nanoparticles that was formed had SPR (Surface Plasmon Resonance) absorbance peak values at the wavelength of about 445,5 nm with an absorbance value of 3,437. The absorbance value increased with the increasing reaction time from 1 hour to 168 hours. From the result of testing using PSA, the average size of silver nanoparticles was 109.1 nm which is dispersed between 1,8 nm – 127,3 nm.